Army of one six American veterans after Iraq - Real, Elisabeth, 1979- (Verlag-Scheidegger & Spiess, 2013)
In Army Of One, photo journalist Elisabeth Real tells the story of six American veterans whose lives have been irreversibly altered by the war in Iraq. All but one of the veterans have been officially diagnosed with post-traumatic stress disorder (PTSD). From 2006?13, Elisabeth Real photographed and interviewed these young men, trying to find out what they have been going through and how, in turn, the consequences of their combat experience have affected their families at home.